Additive solutions differentially affect metabolic and functional parameters of platelet concentrates. Issue 1 (14th August 2015) - Leitner, G. C.; List, J.; Horvath, M.; Eichelberger, B.; Panzer, S.; Jilma‐Stohlawetz, P.
Abstract : Background: Pathogen inactivation (PI) of platelet concentrates with extension of shelf life to 7 days requires the use of platelet additive solutions (PAS). We examined the quality of platelets resuspended in three different PAS stored for up to 7 days. Materials and Methods: Twelve triple adult dose platelet concentrates (PC) were collected using the TrimaAccel ® collection system. Each highly concentrated product was divided into three equal parts, and the additive solutions (Composol ® or SSP+ ® or Intersol ™ ) were added to a final concentration of 56% PAS and 44% plasma. Samples were drawn on days 1, 5 and 7 to measure pH, glucose, lactate dehydrogenase (LDH), lactate, mean platelet volume (MPV) and the aggregation response to collagen and the thrombin receptor agonist peptide‐6. Further, p‐selectin expression on platelets was assessed. Results: No statistically significant changes were observed for pH and MPV during 7 days of storage in all PAS containing PCs, whereas glucose decreased and LDH and lactate increased over time ( P  < 0·05). These changes were particularly evident in Intersol PCs on days 5 and 7 compared with Composol ® PCs or SSP+ ® PCs ( P  < 0·05). Platelets from Intersol PCs exhibited the highest baseline activation of p‐selectin and showed reduced collagen‐ and TRAP‐6‐induced aggregation. Conclusion: Resuspension of platelets in Intersol for 7 days results in increased platelet activation and platelet metabolism compared with SSP+ ® or Composol ® . Further clinical studies are needed to evaluate whether the observed differences in PAS‐PCs affect the recovery rate or the life span of transfused platelets.